2015
DOI: 10.7150/ijbs.12152
|View full text |Cite
|
Sign up to set email alerts
|

Norisoboldine, an Anti-Arthritis Alkaloid Isolated from Radix Linderae, Attenuates Osteoclast Differentiation and Inflammatory Bone Erosion in an Aryl Hydrocarbon Receptor-Dependent Manner

Abstract: Norisoboldine (NOR), the primary isoquinoline alkaloid constituent of the root of Lindera aggregata, has previously been demonstrated to attenuate osteoclast (OC) differentiation. Accumulative evidence has shown that aryl hydrocarbon receptor (AhR) plays an important role in regulating the differentiation of various cells, and multiple isoquinoline alkaloids can modulate AhR. In the present study, we explored the role of NOR in the AhR signaling pathway. These data showed that the combination of AhR antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
(34 reference statements)
0
33
0
Order By: Relevance
“… 14 demonstrate that inflammatory hypoxia is observed in colons of mice with chronic colitis. Norisoboldine (NOR), the primary isoquinoline alkaloid of Radix Linderae, possesses well ability to activate aryl hydrocarbon receptor (AhR) 15 . In addition, it can effectively inhibit systemic inflammation in rats with adjuvant-induced arthritis or collagen-induced arthritis through a gut-dependent manner 16 .…”
Section: Introductionmentioning
confidence: 99%
“… 14 demonstrate that inflammatory hypoxia is observed in colons of mice with chronic colitis. Norisoboldine (NOR), the primary isoquinoline alkaloid of Radix Linderae, possesses well ability to activate aryl hydrocarbon receptor (AhR) 15 . In addition, it can effectively inhibit systemic inflammation in rats with adjuvant-induced arthritis or collagen-induced arthritis through a gut-dependent manner 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In RA, osteoclasts formation and differentiation are closely associated with local bone erosion (Wei et al, ). The previous study has showed that IL‐10 and transforming growth factor‐β1, the cytokines secreted from regulatory T cells, play a key role in suppressing osteoclast differentiation and bone resorption (Xu et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…Triptolide enhances these suppressive effects by promoting the production of IL‐10 and transforming growth factor‐β1 (Xu et al, ). The aryl hydrocarbon receptor participates in the activation and differentiation of osteoclasts (Wei et al, ). Norisoboldine attenuates osteoclast differentiation and bone erosion in an aryl hydrocarbon receptor‐dependent manner (Wei et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
See 1 more Smart Citation
“…This cell line can support osteoclast formation in vitro , by secreting RANKL, OPG, and M-CSF, without supplementation from any other regulatory factors [ 20 ]. The RAW 264.7 monocyte cell line is the most commonly used osteoclast precursor; it is widely used to examine osteoclast formation in vitro [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%